Antithrombotic and Antiatherosclerotic Properties of Olive Oil and Olive Pomace Polar Extracts in Rabbits - Nektaria Tsantila; Haralabos C. Karantonis; Despina N. Perrea; Stamatios E. Theocharis; Dimitrios G. Iliopoulos; Smaragdi Antonopoulou; Constantinos A. Demopoulos (Hindawi Limited, 2007)
Olive oil polar lipid (OOPL) extract has been reported to inhibit atherosclerosis development on rabbits. Olive pomace polar lipid (PPL) extract inhibits PAF activity in vitro and the most potent antagonist has been identified as a glycerylether-sn-2-acetyl glycolipid with common structural characteristics with the respective potent antagonist of OOPL. The aim of this study was to investigate the effect of PPL on early atherosclerosis development on rabbits and to compare it with the antiatherosclerotic effect of OOPL. OOPL and PPL inhibition potency, towards both PAF action and PAF binding, was tested in vitro on washed rabbit platelets. Consequently, rabbits were divided into three groups (A, B, and C). All groups were fed atherogenic diet for 22 days. Atherogenic diets in groups B and C were enriched with OOPL and PPL, respectively. At the end of the experimental time, rabbits were euthanized and aortic samples were examined histopathologically. OOPL and PPL inhibited PAF-induced aggregation, as well as specific PAF binding, with PPL being more potent. Free and bound PAF levels and PAF-AH activity were significantly elevated at the end of the experimental time. Plasma total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides levels were also found increased. Groups B and C exhibited significantly increased values of EC50 compared to group A. Histopathological examination revealed that the development of early atherosclerosis lesions in groups B and C were significantly inhibited compared to group A. Significant differences were noted in the early atherosclerosis lesions between groups B and C, thus indicating that PPL exhibit its anti-atherosclerotic activity by blocking PAF receptor. Specific PAF antagonists with similar in vitro and in vivo bioactivity to those that have been previously reported in OOPL exist in PPL.